Power system security enhancement and loss reduction using the SMART power flow controller - Salah Eldeen Gasim, M. H.; Jasni, Jasronita; Mohd Radzi, Mohd Amran; Hizam, Hashim (IEEE (IEEE Xplore), 2014)
The continuous increase of power demand stresses the system, and adversely affects its security. It may lead to components overload and their outage, voltage decline and its collapse, which may cause entire system blackout. As well, the normal flow of power in transmission lines is not the best possible. In this paper, the Phase Angle Regulator (PAR) and Sen Transformer (ST) are suggested to be used for better utilization of the transmission lines, and to enhance power system security. In this work, the PAR and ST are modelled, and connected in a five bus test system using MATLAB/SIMULINK. The simulation results showed validity of both PAR and ST, and the superiority of ST, since it enhances both power flow and voltage security. Based on the results, the new emerging smart power and voltage control device ST is a very effective tool that can be combined into Smart Grids (SGs). It is found that, usage of ST not only manages line flow congestion and maintains bus voltage, but also increases overall efficiency.